Tumor Cell‐Intrinsic CD96 Mediates Chemoresistance and Cancer Stemness by Regulating Mitochondrial Fatty Acid β‐Oxidation (Adv. Sci. 7/2023). Issue 7 (3rd March 2023) - Li, Jiang; Xia, Qidong; Di, Can; Li, Chunni; Si, Hang; Zhou, Boxuan; Yu, Shubin; Li, Yihong; Huang, Jingying; Lu, Yiwen; Huang, Min; Liang, Huixin; et al.
Abstract : Immunotherapy Immunotherapy using immune checkpoint inhibitors has revolutionized anticancer treatment. In article number 2202956, Qiyi Zhao and co‐workers discover CD96, a novel immune checkpoint protein, expressed in cancer cell exhibit features indicative of both breast cancer stem cells (BCSCs) and chemoresistance. The cover, in the Chinese traditional allusions to idioms, represents "killing two birds with one stone", in which arrow signifies CD96 blocking antibody and eagles signify immune cells and BCSCs, respectively. The image represents CD96 blocking not only increases anti‐tumor immunity but also promotes tumor cell killing by chemotherapeutic drugs.